Pengaruh Konsentrasi Kinetin dan Pikloram Terhadap Induksi Tunas Vanili (Vanilla planifolia Andrews.) Secara In Vitro - Fitrianti, Destri Firlidya; Habibah, Noor Aini (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze the effects of combining kinetin and picloram on the in vitro shoot development of vanilla. The research was conducted at the Plant Tissue Culture Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, from July to November 2024, using a Completely Randomized Design one factorial with 16 treatment combinations and five replications. One nodal explants were taken from the 1st to 6th of Vania variety vanilla plantlets. Parameters observed included days to shoot emergence, shoot growth percentage, shoot length, root length, number of roots, and number of leaves. Data were analyzed using the Kruskal-Wallis test. The results showed that the combination of kinetin and picloram had a significant effect on all observed growth parameters. The treatment without the addition of plant growth regulators (kinetin 0 ppm + picloram 0 ppm) produced the best results across all parameters. Other treatments without picloram also exhibited good growth in at least three main parameters. Therefore, the combination of 0 ppm kinetin and 0 ppm picloram was the most optimal treatment for supporting the in vitro growth of vanilla explants.